Analytical and Computational Simulation Approaches to Design Low Energy Glass Block - Binarti, Floriberta; Istiadji, Agustinus Djoko; Satwiko, Prasasto; Iswanto, Priyo Tri (Makara Journal of Technology, 2011)
Analytical and Computational Simulation Approaches to Design Low Energy Glass Block. An environmentally friendly process was developed to produce a low embodied energy glass block from waste glasses. The energy efficiency of the glass block is represented by its thermal conductance (U)